False promises: The tobacco industry, “low-tar” cigarettes, and older smokers - Cataldo, Janine K. (2008)
OBJECTIVE: To investigate the role of the tobacco industry in marketing to and sustaining tobacco addiction among older smokers and aging Baby Boomers. METHODS: Archival searches of electronic archives of internal tobacco company documents using a snowball sampling approach. Analysis utilizing iterative and comparative review of documents, classification by themes, and a hermeneutic interpretive approach to develop a case study. RESULTS: Based on extensive marketing research, tobacco companies aggressively targeted older smokers and sought to prevent them from quitting. Innovative marketing approaches were used. “Low tar” cigarettes were developed in response to the health concerns of older smokers, despite industry knowledge that such products had no health advantage and did not help smokers quit. CONCLUSION: Tobacco industry activities influence the context of cessation for older smokers in several ways. Through marketing “low-tar” or “light” cigarettes to older smokers at risk at quitting, the industry contributes to the illusion that such cigarettes are safer; however, “light” cigarettes may actually make it harder for addicted smokers to quit. Through targeted mailings of coupons and incentives, the industry discourages older smokers from quitting. Through rhetoric aimed at convincing addicted smokers that they alone are responsible for their smoking, the industry contributes to self-blame, a documented barrier to cessation. Educating practitioners, older smokers and families about the tobacco industry’s influence may decrease the tendency to “blame the victim,” thereby enhancing the likelihood of tobacco addiction treatment for older adults. Comprehensive tobacco control measures must include a focus on older smokers.